Quantum Dots
DOI: 10.1385/1-59745-369-2:185
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Dots in Flow Cytometry

Abstract: The development of new fluorophores has experienced a tremendous advance over the last two decades. The unique photophysical properties of quantum dots (QDs), such as their large Stokes shifts and exceptional brightness, make them attractive probes in flow cytometry applications. In this chapter, the spectral overlap and the fluorescence intensity of a single Qdot nanocrystal species (Qdot-655) was investigated in the context of a panel containing conventional fluorophores. Certain compensation issues remain b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…However, photostability, cytotoxicity and membrane permeability are limiting fluorophore-specific attributes and thus have to be considered carefully. In the last years, several studies focussed on quantum dot (QD) usage for FACS analysis instead of traditional fluorophores due to their narrower emission peaks (Abrams and Dubrovsky 2007) but their application is also limited in cause of often enhanced cytotoxicity (Derfus et al 2004). In this context, nanoparticles recently got in the focus of interest as revolutionary and alternative marker compared to conventional fluorophore dyes.…”
Section: Nano-revolution Of Genetics and Reproductive Biologymentioning
confidence: 99%
“…However, photostability, cytotoxicity and membrane permeability are limiting fluorophore-specific attributes and thus have to be considered carefully. In the last years, several studies focussed on quantum dot (QD) usage for FACS analysis instead of traditional fluorophores due to their narrower emission peaks (Abrams and Dubrovsky 2007) but their application is also limited in cause of often enhanced cytotoxicity (Derfus et al 2004). In this context, nanoparticles recently got in the focus of interest as revolutionary and alternative marker compared to conventional fluorophore dyes.…”
Section: Nano-revolution Of Genetics and Reproductive Biologymentioning
confidence: 99%
“…Staining index is a useful metric detector for normalized fluorescent signal over background. 21 In this study, quantification of staining index for fluorophores clearly showed that QD525 exhibited very low background and hence considerably higher staining index compared to FITC.…”
Section: Discussionmentioning
confidence: 56%
“…state that some DC failed to perform as expected regarding signal intensity and binding specificity in FC and MC . Practically, semiconductor quantum dot nanoparticles (Qdots) also function as DCs, as they are detectable by FC according to their fluorescence properties, and likewise by MC, according to their cadmium content .…”
Section: Discussionmentioning
confidence: 94%